2008
DOI: 10.2109/jcersj2.116.525
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure of Ta- and Al- doped Zn2TiO4 showing oxide ion conduction via cation vacancy

Abstract: To investigate the defect structure of Zn2-x/2Ti1-xTaxO4 and the subsequent oxide ion conduction, equimolar Al 3+ with Ta 5+ have been partly substituted instead of Ti 4+ ions in Zn2TiO4, forming Zn2Ti1-2xTaxAlxO4 with no significant cation vacancy despite of tantalum substation. Inverse spinel-type structured solid solution was approximately formed up to x = 0.3 and the measured powder density agreed with the nominal model where all the cation sites ware almost occupied. A slight decrease in oxide ion conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…5) These values were essentially in agreement with the products of · total and ionic transport numbers t ion obtained from EMFs of oxygen gas concentration cells, 1) which were also plotted by open circles. Moreover, consistent plotting was certainly possible in the aluminum-doped systems with a fixed tantalum content, Zn 1.925+y/2 Ti 0.85¹y Ta 0.15 Al y O 4 4) (open triangle symbols in Fig. 3) and no cation vacancy, Zn 2 Ti 1¹2x -Ta x Al x O 4 (rectangle symbols).…”
Section: ¹1mentioning
confidence: 64%
See 2 more Smart Citations
“…5) These values were essentially in agreement with the products of · total and ionic transport numbers t ion obtained from EMFs of oxygen gas concentration cells, 1) which were also plotted by open circles. Moreover, consistent plotting was certainly possible in the aluminum-doped systems with a fixed tantalum content, Zn 1.925+y/2 Ti 0.85¹y Ta 0.15 Al y O 4 4) (open triangle symbols in Fig. 3) and no cation vacancy, Zn 2 Ti 1¹2x -Ta x Al x O 4 (rectangle symbols).…”
Section: ¹1mentioning
confidence: 64%
“…In the previous experiments on Zn 2¹x/2 Ti 1¹x -Ta x O 4 system, 9),10) the dielectric relaxation behavior was found to be strongly influenced by the change in crystal symmetry, i.e., frequency dependence of the imaginary part of the electric modulus appeared as double peaks when the structure varied from cubic to tetragonal with the tantalum substitution. On the contrary, Zn 2¹(x¹y)/2 Ti 1¹x¹y Ta x Al y O 4 system (x = 0.15) did not show such a phase change due to the introduction of cation vacancy, 4) which were then employed in the present relaxation measurement. Figure 4 showed the typical frequency dependence of the imaginary part of the electric modulus M¤¤ for (a) y = 0 and (b) y = 0.15 samples of Zn 2¹(x¹y)/2 Ti 1¹x¹y Ta x Al y O 4 (x = 0.15).…”
Section: Relaxation Characteristics and Relationship Between The Two mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent interest in Zn 2 TiO 4 as an electronic ceramic that displays ionic conduction has focused on the charge compensation mechanisms exhibited when the material contains excess Ti or is doped with pentavalent Ta ions . The stoichiometric material Zn 2 TiO 4 has an inverse spinel structure with a tetrahedral Zn ion and octahedral Zn and Ti ions.…”
Section: Introductionmentioning
confidence: 99%
“…R ECENT interest in Zn 2 TiO 4 as an electronic ceramic that displays ionic conduction has focused on the charge compensation mechanisms exhibited when the material contains excess Ti 1 or is doped with pentavalent Ta ions. 2,3 The stoichiometric material Zn 2 TiO 4 has an inverse spinel structure with a tetrahedral Zn ion and octahedral Zn and Ti ions. Kim et al 1 have shown that compositions of Zn 2 TiO 4 + xTiO 2 , when equilibrated in air at temperatures above 945°C formed a single-phase Zn 2 TiO 4 structure for x up to~0.33 and attributed the charge compensation mechanism to tetrahedral Zn vacancies.…”
Section: Introductionmentioning
confidence: 99%